Enantioselective organocatalytic aldol reaction of ynones and its synthetic applications. - Silva, F; Sawicki, M; Gouverneur, V (2006)
[Structure: see text] For the first time, unmodified ynones were used in organocatalytic asymmetric aldol reactions delivering monoprotected anti-alpha,beta-dihydroxyynones in high yields, dr's up to 19:1, and ee's up to 95%. These products can be either reduced to afford enantioenriched unsaturated anti,anti-triol or cyclized using a novel intramolecular phosphine-catalyzed alpha-addition to the ynone. This organocatalytic sequential aldol-cyclization process provides a concise entry to unusual enantioenriched oxygenated heterocycles, which can be used for subsequent structural manipulations.